Real-Time Light-Guided Vocal Fold Injection via the Cricothyroid Membrane in Unilateral Vocal Fold Paralysis: A Human Pilot Study - Gene Huh; Pil Geun Jang; Seung Hoon Han; Ramla Talib Mohammad; Woo Jin Jeong; Wonjae Cha (Clinical and Experimental Otorhinolaryngology, 2022)
Objectives. Vocal fold injection (VFI) via the cricothyroid (CT) membrane is used to treat various diseases affecting the vocal folds. The technical challenges of this technique are mainly related to the invisibility of the needle. Real-time light-guided VFI (RL-VFI) was recently developed for injection under simultaneous light guidance in the CT approach. Herein, we present the first clinical trial of RL-VFI, in which we investigated the feasibility and safety of this new technique in unilateral vocal fold paralysis (VFP). Methods. This prospective pilot study enrolled 40 patients, who were treated with RL-VFI for unilateral VFP between September 2020 and August 2021. Adverse events were monitored during the procedure and for 4 weeks postoperatively. The Voice Handicap Index-10, the GRBAS (grade, roughness, breathiness, asthenia, and strain) scale, aerodynamic studies, and acoustic analyses were evaluated to compare the voice improvement after 4 weeks with the baseline values. Results. The needle tip was intuitively identified by the red light. The mean procedure time was 95.6±40.6 seconds for the initial injection, while the additional injection required 79.2±70.5 seconds. The injection was performed under light guidance without additional manipulation after the needle reached the intended point. No acute or delayed adverse events were reported. Among the 40 patients, 36 completed voice analyses after 4 weeks. Subjective and objective voice parameters, including the Voice Handicap Index-10, GRBAS scale, maximum phonation time, mean expiratory airflow, fundamental frequency, jitter, shimmer, and noise-to-harmonics ratio improved significantly after RL-VFI (P<0.05), while the expiratory volume was maintained. Conclusion. RL-VFI is feasible and safe for treating patients with unilateral VFP. This technique is anticipated to improve the precision and safety of the CT approach in the treatment of unilateral VFP. This study provides a rationale for further structured clinical studies.